Development of Nested-Integrated Learning Model in Indonesian Subjects Based on 21st Century Learning - Bahri, Moh. Syaeful; Florentinus, Totok Sumaryanto; Haryono, Haryono (Universitas Negeri Semarang, 2020)
The nested integrated learning model is the integration of curriculum in one discipline, specifically to put the focus of interrogation on several learning skills. The purposes of the study are analyzing the learning models used in Bahasa Indonesia language, developing integrated learning models that are effective in learning Indonesian subjects, improving language skills through a cohesive type of integrated learning model to be implemented in everyday life. This method applied is research and development by Sukmadinata. Data collection techniques used performance test techniques, observations, and interviews. This study applied statistic parametric inferential data. The research and development results showed that the integrated learning model could improve language skills in grade VII students in junior high school. The nested type showed a significant increase in language skills compared to classes with conventional learning. An excess of nested teachers could combine several skills at once in one subject. This model is as an alternative in learning to improve language skills especially. The benefit of this research is to provide a contribution of science and technology in the form of a synthesis study of the Integrated Learning model (nested) type in the Indonesian subjects of class VII.